Exploring the Syntactic Agreement of Verbs with Coordinated Controller Subjects in Najdi Arabic: A Constraint-Based Approach - Althawab, Abdulrahman; Alsanadi, Ruba (Forum for Linguistic Studies, 2025)
Agreement and coordination are linguistic phenomena that exist in all languages. The former refers to the grammatical relationship holding between two or more words or phrases, whereas the latter concerns the process through which two or more expressions are joined together. Each one of these two represents an intriguing topic in linguistics. The current paper attempts to explore a topic that combines them. It investigates the agreement of verbs with coordinated controller subjects in Najdi Arabic (NA). The research problem here is how to identify the appropriate agreement pattern between the verb and the subject, which consists of two coordinated expressions, considering that agreement can also be influenced by different intervening factors. The paper aims to address two research questions. The first is, how do verbs in NA agree with coordinated controller subjects? The second is, how can we theoretically account for this special type of agreement within the constraint-based approach of Head-driven Phrase Structure Grammar (HPSG)? The topic will be studied with a satisfactory amount of naturally occurring data. Among the key findings is that the paper proposes that there are two possible agreement patterns between verbs and coordinated controller subjects in NA. It offers a solid descriptive and theoretical account of these two patterns. The paper delves into the details of this complex type of agreement providing practical insights into understanding agreement and coordination cross-linguistically. This will contribute to the relevant existing literature and provide guidance on how to investigate the interaction of two or more complex linguistic phenomena.